Assessment of large drystone structures on the Ffestiniog Heritage Railway. Issue 2 (4th May 2018) - Ward, Rob
ABSTRACT: The Ffestiniog Railway's drystone retaining walls have far exceeded the expected life of modern drystone structures. The on-site infrastructure team required confidence in the continued operation of the railway as an important feature of North Wales's industrial history and as a tourist attraction. Due to the individual nature of the Ffestiniog's walls, application of a standard structural appraisal method to all structures was not appropriate. Geometric surveys and material testing enabled a structural analysis to be completed using the Thrust Line software (designed by Chris Mundell and Paul McCombie), in order to highlight critical or likely failure modes for these complex structures. This stability check combined with site observation, awareness of contributing factors and the experience of site personnel allows a risk-based, tailored condition appraisal procedure to be developed for each of the Railway's individual drystone walls. In the case of many historic loadbearing drystone structures, complex history, lack of construction records and inability to appraise condition beyond the visible wall face lead to intrusive repair or replacement with a modern alternative, often at significant cost to the asset owner. This piece of work proposed an alternative approach to understanding structural behaviour in order to avoid unnecessary intervention.